Clinical characteristics and risk factors of cardiac surgery associated-acute kidney injury progressed to chronic kidney disease in adults: A retrospective, observational cohort study - Fan, Xiaoguang; Shao, Zehua; Gao, Suhua; You, Zhenzhen; Huo, Shuai; Zhang, Zhu; Li, Qiuhong; Zhou, Saijun; Yan, Lei; Shao, Fengmin; Yu, Pei (Frontiers in Cardiovascular Medicine, 2023)
Introduction To retrospectively investigate the clinical characteristics and risk factors of cardiac surgery associated-acute kidney injury (CS-AKI) progressed to chronic kidney disease (CKD) in adults and to evaluate the performance of clinical risk factor model for predicting CS-AKI to CKD. Methods In this retrospective, observational cohort study, we included patients who were hospitalized for CS-AKI without a prior CKD [estimated glomerular filtration rate (eGFR)<60 mL · min−1·1.73 m−2] at Central China Fuwai Hospital from January 2018 to December 2020. Survived patients were followed up for 90 days, the endpoint was CS-AKI to CKD, and then divided them into two groups (with or without CS-AKI to CKD). The baseline data including demographics, comorbidities, renal function, and other laboratory parameters were compared between two groups. The logistic regression model was used to analyze the risk factors for CS-AKI to CKD. Finally, receiver operator characteristic (ROC) curve was drawn to evaluate the performance of the clinical risk factor model for predicting CS-AKI to CKD. Results We included 564 patients with CS-AKI (414 males, 150 females; age: 57.55 ± 11.86 years); 108 (19.1%) patients progressed to new-onset CKD 90 days after CS-AKI. Patients with CS-AKI to CKD had a higher proportion of females, hypertension, diabetes, congestive heart failure, coronary heart disease, low baseline eGFR and hemoglobin level, higher serum creatinine level at discharge (P<0.05) than those without CS-AKI to CKD. Multivariate logistic regression analysis revealed that female sex(OR=3.478,95%CI:1.844–6.559,P=0.000), hypertension (OR=1.835,95%CI: 1.046–3.220,P=0.034), coronary heart disease (OR=1.779,95%CI: 1.015–3.118, P= 0.044), congestive heart failure (OR=1.908,95%CI:1.124–3.239,P=0.017), preoperative low baseline eGFR (OR=0.956,95%CI:0.938–0.975,P=0.000), and higher serum creatinine level at discharge (OR=1.109, 95% CI:1.014–1.024, P=0.000) were independent risk factors for CS-AKI to CKD. The clinical risk prediction model including female sex, hypertension, coronary heart disease, congestive heart failure, preoperative low baseline eGFR, and higher serum creatinine level at discharge produced a moderate performance for predicting CS-AKI to CKD (area under ROC curve=0.859, 95% CI:0.823–0.896). Conclusion Patients with CS-AKI are at high risk for new-onset CKD. Female sex, comorbidities, and eGFR can help identify patients with a high risk for CS-AKI to CKD.